Explaining the use of related tax instruments - Stanley L. Winer; Walter Hettich (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
A new view is emerging in the economic literature on how to analyze and interpret national and subnational revenue systems. Recent work has shown that such systems can be modelled successfully as sets of related policy instruments that are being shaped and used deliberately by vote-maximizing governments. We extend existing empirical work by estimating a two-equation system designed to investigate the use of related tax instruments by U.S. states. The model focuses on two decisions: how much to rely on personal income as a tax base and whether to introduce an income tax credit or rebate for local property taxes. We also raise some general methodological problems that empirical research in the expected vote-maximizing tradition must deal with in the future.
Keywords: H11; H20; H71; 330; Steuertheorie; Ökonomische Theorie der Demokratie; Theorie